Stratification of deep vein thrombosis and pulmonary embolism risk factors after trauma and orthopedic surgery - G. Sh. Golubev; S. S. Sasko; S. S. Bachurin; D. P. Berezovskiy (Медицинский вестник Юга России, 2018)
The aim of this work is to assess the methods of risk stratification of deep vein thrombosis (DVT) and pulmonary embolism (PE) after trauma and orthopedic surgery. Modern data devoted to risk factors of DVT and PE (including genetic) are uncertaint. We analyzed probability of DVT and PE on the base of literature data for trauma and orthopedic patients. Different models of risk stratification being compared. Single gene mutation is not sig-nificant for DVT risk prediction. Correlations between several gene mutations and polymorphism increase probability of proper risk estimation. Programmatic DVT and HAS risk estimation calculator developed and is accessible on web-site.